Physical Activity: An Underutilized Tool in the Treatment of Mental Illness - Mozaffer Rahim Hingorjo; Sadiqa Syed; Riaz Ahmed Shahid; Lubna Riaz; Fareeha Butt; Nasrul Huda (KARACHI MEDICAL AND DENTAL COLLEGE, 2023)
There are a number of benefits to mental health that have been related to physical activity. Some of these benefits include relief from stress and depression, improved thinking, and an overall improvement in emotional wellbeing. According to a number of studies, people suffering from mental illnesses such as schizophrenia, anxiety disorders, and depression may all respond well to treatments that focus on physical activity. It is possible that including regular exercise as part of one's lifestyle will not only improve one's physical health but will also improve one's mental health and general well-being. Providers of mental health services have an important part to play in encouraging those who suffer from mental illness to engage in physically active pursuits. To have a full understanding of the potential benefits of mixing physical activity interventions with standard mental health therapies, such as psychotherapy and psychopharmacology, additional research is required.